Pharmacologic induction of PGC‐1α stimulates fetal haemoglobin gene expression. (4th February 2022) - Sun, Yanan; Habara, Alawi; Le, Cuong Quang; Nguyen, Nicole; Chen, Raymon; Murphy, George J.; Chui, David H. K.; Steinberg, Martin H.; Cui, Shuaiying
Summary: Sickle cell disease (SCD) is a genetic disorder that affects millions around the world. Enhancement of fetal γ‐globin levels and fetal haemoglobin (HbF) production in SCD patients leads to diminished severity of many clinical features of the disease. We recently identified the transcriptional co‐activator PGC‐1α as a new protein involved in the regulation of the globin genes. Here, we report that upregulation of PGC‐1α by infection with a lentivirus expressing PGC‐1α or by the small‐molecule PGC‐1α agonist ZLN005 in human primary erythroid progenitor CD34 + cells induces both fetal γ‐globin mRNA and protein expression as well as the percentage of HbF‐positive cell (F cells) without significantly affecting cell proliferation and differentiation. We further found that the combination of ZLN005 and hydroxyurea (hydroxycarbamide) exhibited an additive effect on the expression of γ‐globin and the generation of F cells from cultured CD34 + cells. In addition, ZLN005 induced robust expression of the murine embryonic βh1‐globin gene and to a lesser extent, human γ‐globin gene expression in sickle mice. These findings suggest that activation of PGC‐1α by ZLN005 might provide a new path for modulating HbF levels with potential therapeutic benefit in β‐hemoglobinopathies.